Effect dietary vitamins and minerals premix levels on the productive performance of fattening guinea pigs. - Paredes, M. (2023)
The aim of this study was to determine the effect of five levels of inclusion (0, 0.1, 0.2, 0.3 and 0.4%) of a commercial premix of vitamins and trace minerals in the feed on the productive parameters of fattening guinea pigs from 3 to 6 weeks (post-weaning phase) and from 7 to 10 weeks (pre-slaughter phase). Sixty 14-day-old male guinea pigs of the Peru breed were randomly assigned to 20 pens and 5 treatments, under a completely randomized experimental design. The guinea pigs were fed ad libitum with the concentrate and with restricted green forage for eight weeks. In the post-weaning phase, the treatment with 0.1% premix achieved higher body weight, weight gain and feed conversion rate, while there were no differences between treatments in the pre-slaughter phase. The treatment with 0.4% of the premix caused a higher liver weight in the guinea pigs. It is concluded that fattening guinea pigs with mixed feeding only require the premix used during the post-weaning phase.